Comparison of Repair Methods for Ceramic-Fused-to-Metal Crowns - Mutlu ¨Ozcan, DMD, PhD;1 Jeroen M. van der Sleen, DDS;2 Hemmo Kurunm¨aki, (Journal of Prosthodontics, 2006)
The objective of this study was to evaluate the effect of four repair methods on the fracture load of repaired ceramic-fused-to-metal crowns.